Variation in oil contents, and seed and seedling characteristics of Jatropha curcas of West Nusa Tenggara selected genotypes and their first improved population - BAMBANG BUDI SANTOSO (Smujo International, 2011)
Abstract. Santoso BS. 2011. Variation in oil contents and seed and seedling characteristics of Jatropha curcas of West Nusa Tenggara selected genotypes and their first improved population. Nusantara Bioscience 3: 130-135. This study describes variation in seed and seedling characters of Jatropha curcas Linn. of West Nusa Tenggara selected genotypes. Exploration was conducted in several areas where large population of this species grown as fences were found. Five selected genotypes were then grown in experimental fields to let mass selection to obtain the first improved population for each genotype. Seeds of wild population (P0) and those of selected trees as the first improved population (IP-1) were subjected to this study. Seed and seedling characteristics were measured. The result indicated that considerable genetic variability existed among the five J. curcas of West Nusa Tenggara selected genotypes and within each genotype population for seed and seedling characteristics. Genotypes of West Lombok, Sumbawa, and Bima performed exceedingly better than those of Central Lombok and East Lombok. Therefore, this study has suggestions for identifying potential seed sources of J. curcas and these existing genetic variability provides breeders with materials in crop improvement program.